PENGARUH KUALITAS PRODUK, PRESEPSI HARGA DAN LOKASI TERHADAP KEPUASAN PELANGGAN (Studi Pada Cafe Dewan Kopi Pati) - Bayu yudi Oktavian; Euis Soliha (STIE Pelita Nusantara Semarang, 2022)
This study aims to analyze the effect of product quality, price perception and location on customer satisfaction at Cafe Dewan Kopi Pati. The population in this study were the customers of Cafe Dewan Kopi Pati. The research method used is purposive sampling. The sample used was 100 respondents with the primary data collection method using a questionnaire. Data analysis used instrument test, multiple linear analysis and model test. The results of the study prove that product quality has a positive and significant effect on customer satisfaction, price perception has a positive and significant effect on customer satisfaction, location has a positive and significant effect on customer satisfaction.